Marketing Efficiency of Yellowfin Tuna (Thunnus albacares) at Bungus Ocean Fisheries Port, West Sumatra - Fadhila Sahira Erian Putri; Lauura Hermala Yunita; Afriani harahap (Fakultas Perikanan dan Kelautan Universitas Riau, 2026)
The Bungus Ocean Fisheries Port (PPS Bungus) in West Sumatra plays a crucial role in marketing yellowfin tuna (Thunnus albacares). As a fish landing base in western Indonesia, PPS Bungus supports activities including fishing, unloading, sorting, and tuna distribution. The marketing channels involve a series of interdependent institutions that deliver the product to consumers, with varying levels of efficiency and costs. This study aims to understand the marketing channels, marketing efficiency, marketing margins, and price differences of yellowfin tuna at PPS Bungus, West Sumatra. The research was conducted at Bungus Ocean Fisheries Port (PPS) in West Sumatra Province from July 25 to August 16, 2023. The methodology employed in this research involved surveys, data processing using Microsoft Excel, and SPSS version 26. The research findings indicate that there are two marketing channels for yellowfin tuna: one between fishermen and PT. Dempo Andalas Samudera, and another between fishermen and PT. Lintas Laut Samudera. The marketing margin for yellowfin tuna at PT. Dempo Andalas Samudera is IDR 12,000, and at PT. Lintas Laut Samudera is IDR 13,000. The fishermen's Share at PT. Dempo Andalas Samudera is 74.46%, and at PT. Lintas Laut Samudera is 72.91%. The efficiency of the marketing channels for yellowfin tuna shows 1.17 for PT. Dempo Andalas Samudera and 1.14 for PT. Lintas Laut Samudera. This study demonstrates that the marketing channels at PPS Bungus are efficient, and there are no differences in selling prices between PT. Dempo Andalas Samudera and PT. Lintas Laut Samudera